The insider [videorecording (DVD)] - Mann, Michael, 1943-; Pacino, Al, 1940-; Crowe, Russell, 1964-; Plummer, Christopher; Venora, Diane; Hall, Philip Baker, 1931-2022; Crouse, Lindsay; Mazar, Debi; Tobolowsky, Stephen, 1951-; Feore, Colm, 1958-; McGill, Bruce, 1950-; Gambon, Michael; et al. (Touchstone Home Video : Distributed by Buena Vista Home Entertainment, 1999)
When former executive Jeffrey Wigand is fired by his employer, one of the largest tobacco companies in America, Wigand agrees to become a paid consultant for a story by veteran 60 minutes producer Lowell Bergman, regarding alleged unethical practices within the tobacco industry. But what begins as a temporary alliance leads to a lengthy battle for both men to save their reputations and more.